Effect of wearing complete dental prosthesis on candidal count - Bhargava, Ankur; Saigal, Sonal (International Journal of Research in Medical Sciences, 2017)
Background: Infection due to fungi have increased dramatically in recent years and are of prime importance because of the rising number of immunocompromised patients, such as cancer patients receiving chemotherapy, and human immunodeficiency virus infected patients. The aim of the analysis was to compare the candidal count at the time of insertion and after one month of wearing complete dentures. Methods: It was a quasi-experimental study which consisted of forty edentulous patients with no previous denture history. They obtained new complete dentures. Samples were taken using the oral rinse technique and cultured on sabouraud agar for fungal growth and cultured positive samples had undergone for germ tube test in serum media. Results: Candidal colonies were detected and counted as colony forming units at the time of insertion and after one month of wearing complete dentures. Change in candidal count was significantly higher after one month of wearing complete dentures (p=0.0001). Difference in candidal count was significantly higher in females than males. Conclusions: Candidal count was significant after wearing complete dentures and this should be considered as an important factor that can pre-dispose the patients to candida induced denture stomatitis.